2020
DOI: 10.1111/imr.12897
|View full text |Cite
|
Sign up to set email alerts
|

The role of host genetics in the immune response to SARS‐CoV‐2 and COVID‐19 susceptibility and severity

Abstract: This article provides a review of studies evaluating the role of host (and viral) genetics (including variation in HLA genes) in the immune response to coronaviruses, as well as the clinical outcome of coronavirus‐mediated disease. The initial sections focus on seasonal coronaviruses, SARS‐CoV, and MERS‐CoV. We then examine the state of the knowledge regarding genetic polymorphisms and SARS‐CoV‐2 and COVID‐19. The article concludes by discussing research areas with current knowledge gaps and proposes several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
196
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(210 citation statements)
references
References 131 publications
1
196
0
6
Order By: Relevance
“…The study also confirmed the potential importance of ABO blood group antigens for virus infection and disease: higher risk for blood group A and a lower one for blood group O as compared with other blood groups [109]. There are data that specific HLA polymorphisms are related to the susceptibility and protection from SARS-CoV-1 infection [110,111]. Authors have suggested that epigenetic dysregulation of ACE2 and interferon-regulated genes is associated with increased COVID-19 susceptibility and severity in lupus patients [112].…”
Section: Host Factorssupporting
confidence: 58%
“…The study also confirmed the potential importance of ABO blood group antigens for virus infection and disease: higher risk for blood group A and a lower one for blood group O as compared with other blood groups [109]. There are data that specific HLA polymorphisms are related to the susceptibility and protection from SARS-CoV-1 infection [110,111]. Authors have suggested that epigenetic dysregulation of ACE2 and interferon-regulated genes is associated with increased COVID-19 susceptibility and severity in lupus patients [112].…”
Section: Host Factorssupporting
confidence: 58%
“…39,40 Thus, the literature published during the execution of this study confirms the conjecture that SNPs in FPR1 have no major disease-modulatory role in COVID-19. 41 In conclusion, neither rs867228 nor rs5030880 affects the severity of the clinical course of COVID-19. It appears plausible to speculate that polymorphisms affecting the function of PRRs such as FPR1 or Toll-like receptors are prevalent in the population to create heterogeneity in the response to major life-threatening infectious pathogens, avoiding, for example, excessive inflammatory responses in a fraction of the population.…”
Section: Resultsmentioning
confidence: 85%
“…Research in this area is only in its infancy. Also building on previous experience with other Coronaviridae, several studies are investigating the link between SARS and genetic variants in innate immune response ( 28 ), including mannose‐binding lectin deficiency and polymorphisms, which are involved in the inactivation of a variety of respiratory pathogens through direct binding and complement activation ( 29 ). Similarly, adaptive immune dysfunction is appearing as a key, and recent studies have confirmed the role of CD3 + T cell cytopenia in determining COVID-19 progression and fatality ( 30 ).…”
Section: The Complex Interplay Between the Viral Burden Innate Andmentioning
confidence: 99%